Paranoid explanations of experience: a novel experimental study. - Green, C; Freeman, D; Kuipers, E; Bebbington, P; Fowler, D; Dunn, G; Garety, P (2011)
BACKGROUND: Paranoia is a common experience in the non-clinical population. We use a novel experimental methodology to investigate paranoid ideas in individuals without a history of mental illness. AIMS: We aimed to determine whether this paradigm could elicit unfounded paranoid thoughts and whether these thoughts could be predicted by factors from a cognitive model. METHOD: Fifty-eight individuals took part and completed measures assessing trait paranoia, mood, self and other schema and attributional style. They were exposed to two experimental events: 1) an interruption to the testing session by a stooge, and 2) a recording of laughter played outside the testing room and subsequently asked about their explanations for these events. RESULTS: 15.5% (n = 9) of the sample gave a paranoid explanation for at least one of the experimental events. The remainder reported generally neutral explanations. Individuals with a paranoid explanation reported significantly higher levels of trait paranoia. Factors predictive of a paranoid interpretation were interpersonal sensitivity and attributional style. CONCLUSIONS: The results show that spontaneous paranoid explanations can be elicited in non-clinical individuals, even for quite neutral events. In line with current theories, the findings suggest that emotional processes contribute to paranoid interpretations of events, although, as a novel study with a modest sample, it requires replication.